Physical activity and risk behaviors among adolescents: the mediating roles of diet, sleep, mental health, and substance use - Tian, Feng; Liu, Fengbo (Frontiers in Public Health, 2025)
BackgroundSuicide risk (SR), including suicidal ideation and suicide attempts, is a critical public health issue, particularly among adolescents. Emerging evidence highlights substance use risk (SUR) as a prominent factor elevating SR among youth. Physical activity (PA) has demonstrated protective effects against both SR and SUR, potentially due to its broad benefits for physical and mental well-being. Despite accumulating evidence supporting these associations, the underlying mediating mechanisms remain poorly understood, especially the roles of sleep duration (SD), healthy diet (HD), and mental health (MH). Clarifying the complex interactions and sequential mediating pathways among these variables is essential for developing effective interventions to mitigate SR and SUR among adolescents.MethodsWe analyzed data from the 2023 U.S. Youth Risk Behavior Surveillance System (YRBSS), including 15,734 adolescents after excluding cases with missing key variables. PA, HD, SUR, SR, SD, and MH were measured using validated YRBSS items, with multi-item constructs modeled as latent variables. Structural equation modeling and bootstrapped mediation analyses (5,000 resamples) were conducted in R 4.5, with model fit evaluated using RMSEA (< 0.08) and CFI/TLI (> 0.95).ResultsHigher PA significantly predicted lower SR (β = −0.024, p < 0.001) and SUR (β = −0.021, p < 0.001). Notably, direct pathways from PA to SR and SUR revealed small positive effects, indicating suppression effects and emphasizing the importance of indirect mechanisms. MH emerged as a crucial mediator between PA and both SUR and SR. Additionally, SD significantly mediated the association between PA and SUR. Chain mediation analyses revealed significant sequential pathways: PA → SD → MH → SUR; PA → MH → SUR → SR; and PA → HD → MH → SR, highlighting complex protective mechanisms linking physical activity with adolescent health outcomes. Conversely, HD alone did not significantly mediate the PA–SR relationship, and the PA → SD → SUR → SR pathway was not supported.DiscussionThe beneficial effects of PA on reducing SR and SUR among adolescents primarily operate indirectly through enhanced MH and SD, with minor contributions from dietary habits. These findings underscore the importance of integrated intervention strategies targeting MH and sleep quality to maximize the protective benefits of PA for adolescents.